Corporate foresight: A bibliometric analysis on research trends - Chichorro, Eurico Caldas Fernandes de Sousa (2022)
The pressure on companies, influenced by the rapid dissemination of technological innovations increased the volatility of business environments making difficult for companies to decide and act when faced with market uncertainties. Corporate foresight (CF) is a fundamental management tool, which has been object of study in recent decades. CF enables companies to achieve better market position, sustainable profits and ultimately provides competitive advantages in the medium/long term, while also dealing positively with uncertainty. This research aims to identify investigate trends in CF based on previous studies. From a query created in Web of Science (WoS), we obtained our initial data sample, comprised between the period 2001 to 2021. Thus, allowing us to study the frequency of publications and total citations, as well as descriptively study journals, authors, keywords, and references. We then carried out a bibliometric analysis using CiteSpace software to study research patterns and trends. The results of the bibliometric analysis suggest a progressive interest in open foresight and the opportunity for new explanatory research as a method for understanding and validating corporate foresight.